DAMPAK IMPLEMENTASI PENGEMBANGAN BUDAYA MUTU AKADEMIK RELIGIUS KEPALA MADRASAH DALAM MEMBANGUN SIKAP SOSIAL - Muhammad Husni (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2020)
Quality culture is manifested in the form of development which includes two main elements, namely: cultural fostering which includes vision, mission, goals, values and beliefs, reward systems, emotional and social relationships, and madrasah design. then personal development in the form of role models, including personal behavior, principal behavior and administrative action. The purpose of this study is to analyze and find the impact of the application of quality culture development in MAN Gondanglegi, MAN Turen, and MA Raudlatul Ulum Ganjaran Gondanglegi. This research method uses a qualitative approach with type of study designed with multi-case. Data were collected through in depth interview and participant observation and documentation study. The data analysis technique used individual case analysis and cross-case analysis. And data validity checking activities include credibility, dependability, and confirmability. The result, the development of a quality culture has an impact on the attitudes and behavior of Madrasah principals in building relationships with educators, the community, stakeholders in a harmonious and holistic manner, with academic achievement so that customers can trust them.